Taksonomi Nilai Adab QS Al-Hujurat 11 sebagai Basis Preventif Bullying: Kajian Tafsir Muqaran - ZULFAN SYAHANSYAH; LINDA PUSPITASARI (JURNAL ILMIAH RESEARCH STUDENT, 2026)
Bullying in Islamic educational institutions is often addressed through regulation or post-incident counseling, while preventive value frameworks firmly grounded in Qur'anic text remain underdeveloped. This study analyzes the taxonomy of adab values in QS. Al-Hujurat verse 11 and formulates its relevance as a preventive framework for bullying. The study employs a qualitative library research approach using tafsir muqaran, comparing interpretations across five authoritative exegeses spanning different methods and eras, namely At-Tabari, Al-Baghawi, Ibn Kathir, As-Sa'di, and Al-Wasith, followed by a descriptive-analytical review of contemporary academic literature. The findings formulate four interlocking adab values: tawadhu' and tasamuh derived from the prohibition against mockery, ukhuwah with passive-active dimensions derived from the prohibition against defamation, and ihsan derived from the prohibition against abusive nicknames. The highest interpretive convergence appears in the prohibition against defamation. This taxonomy operates more concretely than maqashid-based approaches and offers a preventive function distinct from post-incident counseling models.